Synopsis of a clinical practice guideline for pancreatic ductal adenocarcinoma with peritoneal dissemination in Japan; Japan Peritoneal Malignancy Study Group. (7th January 2022) - Satoi, Sohei; Takahara, Naminatsu; Fujii, Tsutomu; Isayama, Hiroyuki; Yamada, Suguru; Tsuji, Yasushi; Miyato, Hideyo; Yamaguchi, Hironori; Yamamoto, Tomohisa; Hashimoto, Daisuke; Yamaki, So; Nakai, Yousuke; et al.
Abstract: Patients with pancreatic ductal adenocarcinoma (PDAC) with peritoneal dissemination have a dismal prognosis because discontinuation of systemic chemotherapy is required for massive ascites or poor performance status. The natural history, diagnosis and treatment of PDAC with peritoneal dissemination have not been fully investigated. We systematically reviewed published information on the clinical diagnosis and treatment of PDAC with peritoneal dissemination using the PubMed database (2000‐2020) and provided recommendations in response to clinical questions. This guideline was created according to the "Minds Clinical Practice Guideline Development Guide 2017". The literature quality and body of evidence were evaluated with the GRADE System and classified into four levels ("strong", "medium", "weak", "very weak"). The strength of each final recommendation was decided by a vote of committee members based on the GRADE Grid method. These guidelines address three subjects: diagnostic, chemotherapeutic, and surgical approaches. They include nine clinical questions and statements with recommendation strengths, evidence levels, and agreement rates, in addition to one "column". This is the English synopsis of the 2021 Japanese clinical practice guideline for PDAC with peritoneal dissemination. It summarizes the clinical evidence for the diagnosis and treatment of PDAC with peritoneal dissemination and provides future perspectives. Abstract : Highlight On behalf of the Japan Peritoneal Malignancy Study Group, Satoi and colleagues present an English synopsis of the 2021 Japanese clinical practice guidelines for pancreatic ductal adenocarcinoma with peritoneal dissemination. It summarizes the clinical evidence for the diagnosis and treatment of pancreatic ductal adenocarcinoma with peritoneal dissemination and provides future perspectives.